Estratégias de geração de valor no negócio de semente de soja no sudeste de Mato Grosso - Andrade, Márcio Eduardo Forti Ribeiro de (2011)
The relationship with clients allied to a clear and well defined strategy constitutes in the soybean market critical success factors for a breeder company. Thus, the present study has, as the main objective to assess if the actions adopted by TMG company do represent efficient instruments to the improvement of its competitiveness, and to analyze the results of such strategy to recover market share, from the aspect of value creation and a relational perspective among the company and its clients. In order to reach that, it was used the methodology of exploratory case study, based on theories of value generation and marketing strategies with data obtained through four consecutive crops. Demonstrative units, observation units, maximum productive project, commercial area collection, strategic analysis of distributors, informal meetings and field days were the marketing strategies used. The results obtained were the increase of marketing share in three cultivars from the total of four, during three crops, the increase of marketing share of 70% in a group of client / productors in a period of two crops and the increase in the marketing share of distributors of Southeast region of 47% between the crops 2007/08 and 2011/12. As a final result there is an increase in the seed marketing share of the Southeast Region of 34% from the 2007/08 crop to 2011/12 crop. It can be concluded that the relational marketing strategies during four crops effectively helped the studied company to generate value, resulting in the increase of seed marketing share of the Southeast Region of Mato Grosso.